Oviposition Preference and Developmental Performance of Drosophila suzukii on Different Cherry Cultivars - Fan Yang; Haikuan Sun; Zehua Wang; Jingxia Xie; Jingyan He; Guanghang Qiao; Jing Wang; Yuyu Wang; Shanning Wang (Insects)
Drosophila suzukii is a major pest of sweet cherries. In this study, we evaluated its oviposition preferences across six cherry cultivars and assessed the effects of the fruit traits on its growth and development. Significant differences in the color, firmness, and sugar content were observed among the cultivars and ripeness stages. The highest oviposition rates were recorded for the “Hongdeng” (HD) and “Burlat” (BLT) cultivars in both the non-choice (HD: 31.9 ± 2.0 eggs/cherry; BLT: 31.3 ± 1.9 eggs/cherry) and choice (HD: 32.4 ± 3.2 eggs/cherry; BLT: 27.6 ± 1.9 eggs/cherry) tests, largely influenced by the fruit color. While the developmental parameters showed slight variation across the cultivars, significant differences were observed in the pupation rates (ranging from 0.80 to 0.89) and survival rates (ranging from 0.51 to 0.62), with both parameters being the highest for the “Hongdeng” cultivar. The correlation analysis revealed that a darker fruit color—characterized by lower lightness (L*), lower chromaticity (b*), and a higher color index for red grapes (CIRG)—positively influenced the oviposition and pupation rates. Although the other correlations were not significant, the oviposition and developmental parameters were positively correlated with sweetness and negatively correlated with firmness. These findings enhance our understanding of how cherry traits influence D. suzukii behavior, providing critical insights for pest management strategies in cherry production.